Detrimental Effect of Bovine Serum Albumin in a Maturation Medium on Embryonic Development after Somatic Cell Nuclear Transfer in Pigs - Hanna Lee; Yongjin Lee; Bola Park; Fazle Elahi; Joohyeong Lee; Jung Hoon Choi; Seung Tae Lee; Choon-Keun Park; Sang-Hwan Hyun; Eunsong Lee (The Korean Society of Animal Reproduction and Biotechnology, 2014)
This study was designed to evaluate the effect of bovine serum albumin (BSA) in a maturation medium on oocyte maturation and embryonic development in pigs. Immature pig oocytes were matured for 44 h in a medium supplemented with 0.4% (w/v) BSA, 0.1% (w/v) polyvinyl alcohol (PVA), or 10% (v/v) pig follicular fluid (PFF). After IVM, oocytes reached metaphase II stage were activated for parthenogenesis (PA) or used as cytoplasts for somatic cell nuclear transfer (SCNT). Nuclear maturation (89.5%, 90.7% and 91.3% for BSA, PVA and PFF, respectively) and intraoocyte glutathione contents (1.20, 1.16 and 1.00 pixels/oocyte for BSA, PVA and PFF, respectively) were not altered by the macromolecules added to maturation medium. IVM of oocytes in a medium containing BSA (21.4%) and PVA (20.7%) showed significantly lower blastocyst formation after PA than culture in medium with PFF (39.2%). After SCNT, oocytes matured in medium with BSA showed decreased embryonic development to the blastocyst stage (9.2%) compared to those matured in medium with PFF (28.9%), while 23.6% of SCNT oocytes matured in medium with PVA developed to the blastocyst stage. When the effect of BSA in a maturation medium during the first 22 h and the second 22 h of IVM in combination with PFF or PVA was examined, PVA-BSA showed a higher nuclear maturation (94.1%) than BSA-PFF (84.5%). However, there was no significant difference in the blastocyst formation among tested combinations (47.3, 52.2, 50.0, 44.4 and 49.0% for PFF-PFF, PFF-BSA, PVA-BSA, BSA-PVA and BSA-PFF, respectively). Our results demonstrate that BSA and PVA added to maturation medium can support oocyte maturation comparable to PFF-supplemented medium. However, maturation of oocytes in a BSA-containing medium decreases embryonic development after PA and SCNT when compared with the medium supplemented with PFF.